Analisis Pemanfaatan Media Sosial Instagram Sebagai Media Promosi Usaha Menantea - Fitria Anggraeni, Anggi; Sudrajat, Ajat; Salsabila , Ailsa Nathania (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The development of social media marketing at this time has grown rapidly. In this modern era, companies can easily use social media as a means of promotion with the aim of increasing brand awareness. With the existence of very tight market competition, each company must be able to keep abreast of existing developments. Instagram social media is a promotional platform that entrepreneurs can use to carry out their digital marketing. In this study, it was found that Menantea uses Instagram as its publication medium and in its implementation, Menantea focuses on information and stories through their Instagram social media.